Study if transition of Indian Education System - Dr Rita (Innovative Research Thoughts, 2018)
Training has been made too simple for students to access the scope of the country's educational system. Advertisements such as the abolition of compulsory CBSE Class 10 from 2010-11, the adoption of a scoring scheme, the transition of children's right to free and compulsory education, reserve policies etc. Are there few of them? The question now emerges as to how effective these interventions in the field of education have been in various states of the world. Haryana is the state with a 3.7 percent share of India's overall GDP. This present thesis would shed light on Haryana's education system and look at its neighbours. An overview of these states' pedagogical accomplishments from various viewpoints will help analysts and scholars realise how far we have come to meet our goals and what needs to be accomplished. In addition, a distinction was made of the literacy rates and literacy rates of those countries.